Radiometric evaluation of natural radioactivity and radiation hazard indices in soils from quarries sites in southwestern Nigeria - Ademila, Omowumi; Ugo, Raphael (International Journal of Advanced Geosciences, 2017)
Quarry activities increase the radiation dose received by humans by distributing the radionuclides associated with the natural resources to the soil surfaces. This study assessed the level of natural radiations in soils around two quarry sites to a maximum depth of 2.0 m and up to 500 m away from the sites. Activity concentration of 232Th, 238U and 40K in twenty soil samples collected from the quarries in Ondo State were measured by means of high resolution gamma-ray spectrometry. Average value of 232Th, 238U and 40K measured were 0.0027±0.0003 Bq/kg and 0.0036±0.00036 Bq/kg, 0.028±0.0012 Bq/kg and 0.026±0.0012 Bq/kg and 47.45±0.0313 Bq/kg and 69.42±0.0313 Bq/kg respectively. The estimated absorbed dose rates in all the soils investigated ranged from 0.38 nGy/hr to 15.67 nGy/hr and the annual mean effective dose equivalent varied from 2.13 to 10.28 µSv/yr. The results revealed that the activity concentrations and radiological hazard indices when compared with their corresponding world permissible values are less than the recommended safe levels. This indicates that quarry activities in the areas have not enhanced the background radiation level of the areas. Regular exposure of the quarry workers and the people around the study areas pose no health hazards in the near future.
Keywords: Activity Concentrations; Quarries; Radionuclides; Radiological Hazard Indices; Soils.